Is there a relationship between fiscal sustainability and currency crises? International evidence based on causality tests - Alexis Cruz-Rodríguez (International Journal of Economic Sciences and Applied Research, 2014)
This paper uses Granger causality tests on a fiscal sustainability indicator (FSI) and currency crises for 17 countries to evaluate the direction of causality between the FSI and currency crises. The FSI developed by Croce and Juan-Ramón (2003) is used. Also, different definitions for currency crises are used to evaluate whether they induce different results in the analysis. In general, the results suggest evidence of causality between the lagged FSI and currency crises.
Keywords: F31; F33; E62; 330; Currency crisis; foreign exchange; fiscal sustainability; Granger causality